Phylogeny of the Andean genus Deprea (Physalideae, Solanaceae): testing the generic circumscription - Carrizo García, Carolina; Wahlert, Gregory; Orozco, Clara Inés; Barboza, Gloria Estela; Bohs, Lynn (Phytotaxa, 2015)
Deprea (Solanaceae) is a small South American genus of 10 species occurring in Andean areas from Venezuela to Bolivia. The circumscription of Deprea has been repeatedly modified in recent years, with new species being described and others transferred into or out of the genus. The relationships of Deprea to other genera of Solanaceae are still poorly understood, although it seems to be closely related to Larnax. A phylogenetic analysis was performed to test the monophyly of Deprea. Sequences from three molecular markers (nuclear ITS and waxy and chloroplast psbA-trnH) were analyzed by parsimony and Bayesian methods. All the species of Deprea and Larnax sampled were intermixed in a strongly supported clade in the consensus trees, and therefore the currently recognized Deprea species do not form a monophyletic group. At least four strongly supported clades could be recovered within the Deprea + Larnax assemblage, but the affinities of several species of both genera remained unresolved. Additional sampling including the majority of the Deprea + Larnax species and more representatives of genera in the Physalideae should be done to clarify relationships within the clade and to pinpoint the closest relatives of Deprea + Larnax.